SELF-INITIATED EXPATRIATES: BIBLIOMECTRIK ANALYSIS - Readi, Robbi; Churiyah, Madziatul; Zagladi, Arief Noviarakhman (PREDIKSI : Jurnal Administrasi dan Kebijakan, 2025)
AbstractThis article reviews the phenomenon of self-initiated expatriates which is an important subject in global mobility studies. This article uses a systematic literature review which aims to summarize several studies regarding Self-Initiated Expatriates. This article uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method and bibliometric analysis using VOSviewer Software. Data sources were obtained from ScienceDirect and Emerald Insight for the 2019-2024 period. The results obtained were 2,974 articles, then data reduction was carried out using exclusive and inclusive criteria to obtain 31 journals that were reviewed. Results for variables related to self-initiated expatriates, Cross-cultural Adjustment, Cultural Intelligence, Social Support, Organizational Citizenship Behavior, Job Demand Resources, Effort reward imbalance, Political skills etc. With a deeper understanding of the dynamics of self-initiated expatriates, this article provides valuable insights for managers, human resource practitioners, and academics in managing and supporting voluntary international mobility and leveraging the valuable contributions that self-initiated expatriates bring to the context of ever-changing global environment.